Impacts of climate change on aquatic insects in temperate alpine regions: Complementary modeling approaches applied to Swiss rivers. (20th May 2021) - Timoner, Pablo; Fasel, Marc; Ashraf Vaghefi, Seyed Saeid; Marle, Pierre; Castella, Emmanuel; Moser, Frédéric; Lehmann, Anthony
Abstract: Freshwater biodiversity loss is a major concern, and global warming is already playing a significant role in species extinctions. Our main goal was to predict climate change impacts on aquatic insect species distribution and richness in Swiss running waters according to two climate change scenarios (RCP2.6 and RCP8.5), using different modeling approaches, that is, species distribution models (SDMs), stacked‐SDMs (S‐SDMs) and a macroecological model (MEM). We analyzed 10, 808 reaches, used as spatial units for model predictions, for a total river network length of 20, 610 km. Results were assessed at both the countrywide and the biogeographic regional scales. We used incidence data of 41 species of Ephemeroptera, Plecoptera and Trichoptera (EPT) from 259 sites distributed across Switzerland. We integrated a coupled model for hydrology and glacier retreat to simulate monthly time‐step discharge from which we derived hydrological variables. These, along with thermal, land‐cover, topographic and spatially explicit data, served as predictors for our ecological models. Predictions of occurrence probabilities and EPT richness were compared among the different regions, periods and scenarios. A Shiny web application was developed to interactively explore all the models' details, to ensure transparency and promote the sharing of information. MEM and S‐SDMs approaches consistently showed that overall, climate change is likely to reduce EPT richness. Decrease could be around 10% in the least conservative scenario, depending on the region. Global warming was shown to represent a threat to species from high elevation, but in terms of species richness, running waters from lowlands and medium elevation seemed more vulnerable. Finally, our results suggested that the effects of anthropogenic activities could overweight natural factors in shaping the future of river biodiversity. Abstract : Prediction of climate change impacts on Ephemeroptera, Plecoptera and Trichoptera (EPT) species distribution and richness in Swiss rivers and streams, using different modeling approaches, i.e. species distribution models (SDMs), stacked‐SDMs (S‐SDMs) and a macroecological model (MEM). MEM and S‐SDMs approaches consistently showed that climate change is likely to reduce EPT richness. Decrease could be around 10% in the least conservative scenario, depending on the region. Global warming was shown to represent a threat to species from high elevation, but in terms of species richness, running waters from lowlands and medium elevation seemed more vulnerable. ​